Fracturing interference behavior and mechanism of deep coalbed methane horizontal wells in the Daning-Jixian Block - Haiyan CHAO; Ze LI; Huaibin ZHEN; Lele GUO; Hui ZHANG (Meitan kexue jishu)
In order to accurately understand the effects of fracturing interference on deep CBM horizontal wells, 18 groups of fracturing interference events and their effects on 18 disturbed wells and 13 interfering wells in Daning-Jixian block were systematically analyzed, the mechanism and key influencing factors of fracturing interference were revealed. The results show that: After the producing well is disturbed, the typical characteristics are the acceleration of wellhead pressure, the decrease of gas production and the sudden increase of liquid production. The gas production recovery degree of disturbed well directly reflects the light and heavy degree of fracturing interference. The lower the cumulative gas production before disturbed, the higher the gas production recovery degree of disturbed well. In the interference event in the direction of well spacing (vertical horizontal section track direction), the lower the fracturing fluid volume and sand volume in the interfering well, the higher the recovery degree of gas production in the disturbed well. Compared with the disturbed well in the interference event of the well spacing direction, the disturbed well in the interference event of the row spacing direction (the same direction as the horizontal segment trajectory) has a higher gas production recovery degree. In the interference event of the row spacing direction, the disturbed well near the target (point A) of horizontal segment of the interfering well has a higher gas production recovery than the disturbed well at the end of the horizontal segment (point B). The formation energy exhaustion degree of the disturbed well, the microstructure, ground stress and reservoir anisotropy of the interfering well work together to affect the fracture pattern of the interfering well. The main factor affecting the production of interfering well is its own fracturing parameters. Compared with the adjacent well without interference on the same well platform, the smaller the section length, the larger the amount of liquid and sand added in a single section of the interfering well, the higher the production is. Finally, theoretical analysis and exploration were conducted on the mechanism of fracturing interference. Fracturing interference mainly has two effects on the disturbed production wells: first, it breaks the dynamic balance of gas water phase permeability, significantly increases water production, and after the discharge of foreign liquids, the gas production can be restored to the pre disturbance gas production level; the second issue is that solid particles such as proppants and coal powder block the pore throats, reducing the flow capacity of the mesh and making it difficult to restore gas production to its original level.